Successful Surgical Management of Partial Obstructive Ileus Secondary to Intra-abdominal Tumor: A Case Report - Bambang Irwansyah; Ida Bagus Budhi Surya Adnyana (Open Access Indonesian Journal of Medical Reviews, 2025)
Partial obstructive ileus, characterized by incomplete intestinal blockage, can arise from various etiologies, including intra-abdominal tumors. These tumors, often compressing or obstructing the bowel lumen, necessitate prompt diagnosis and intervention to prevent severe complications. This case report presents a 42-year-old woman with partial obstructive ileus secondary to an intra-abdominal tumor, highlighting the diagnostic process, surgical management, and clinical outcomes. A 42-year-old female presented to the emergency department with abdominal distension, pain, and a two-day history of constipation. Physical examination revealed abdominal tenderness, and radiographic imaging confirmed partial obstructive ileus with pneumoperitoneum. Initial management focused on hemodynamic stabilization, fluid resuscitation, and nasogastric decompression. Subsequently, an exploratory laparotomy was performed, revealing an intra-abdominal tumor causing intestinal obstruction. Segmental tumor resection was successfully conducted, alleviating the obstruction. In conclusion, this case underscores the importance of considering intra-abdominal tumors in the differential diagnosis of partial obstructive ileus. Timely surgical intervention, including tumor resection, can effectively address the obstruction and improve patient outcomes. Further research is warranted to explore the long-term outcomes and prognostic factors associated with this condition.